THE VALUES OF PLURALISM IN ISLAMIC RELIGIOUS EDUCATION: A PERSPECTIVE FROM AL-QASIMI’S EXEGESIS - Susanti Sangidah; Enjang Burhanudin Yusuf (Jurnal Konseling Pendidikan Islam, 2026)
This study examines the values of pluralism in Islamic religious education through the perspective of Al-Qasimi’s exegesis (Mahasin at-Ta’wil). This study stems from the reality of diversity in Indonesian society, which demands a religious understanding that is inclusive, tolerant, and in harmony with the social context. The research method used is descriptive-analytical with a qualitative approach based on a literature review, with the primary source being Al-Qasimi’s interpretation of Qur’anic verses related to pluralism and tolerance. The analysis reveals that Al-Qasimi interprets verses on pluralism in a moderate and rational manner. Through Surah Al-Hujurat: 13, he emphasizes human equality and the importance of mutual understanding (ta’aruf) as the purpose of diversity. In Surah Al-Kafirun: 6, he affirms the principle of religious freedom without coercion. Meanwhile, in QS. Al-An’am: 108, he highlights the ethics of interfaith dialogue and the prohibition against denigrating other beliefs to maintain social harmony. These values of pluralism have strategic implications for Islamic religious education, particularly in shaping students’ character to respect differences, uphold justice, and engage in polite dialogue with various groups. Thus, the Al-Qasimi Exegesis makes a significant contribution to the development of moderate, humanistic Islamic education that is responsive to the challenges of diversity in the modern era.